Pembuatan Dan Pemanfaatan Blog Bagi Guru Pendidikan Agama Islam Bengkulu Tengah - Hari Aspriyono; Herlina Latipa Sari; Rizka Tri Alinse; Riska Riska; Hendri Alamsyah (Universitas Dehasen Bengkulu, 2023)
One web-based platform that can be utilized is a blog, which enables users to publish information, share learning materials, and communicate online. However, some teachers who are members of the Islamic Religious Education Teachers Working Group (KKG PAI) in Region III of Central Bengkulu Regency still face limitations in utilizing information technology, particularly in creating and managing blogs. This community service activity aims to provide training on creating and utilizing blogs as an information medium for Islamic Religious Education teachers. The implementation method includes several stages: needs analysis, system design, blog development, system testing, and blog usage training. The results indicate that the KKG PAI blog for Region III Central Bengkulu was successfully developed and can function as a platform for disseminating organizational information and sharing knowledge among teachers. In addition, the training activities improved teachers’ knowledge and skills in utilizing information technology to support educational activities and organizational communication.